Factors Influencing Students’ Selection of Home Science in Public Secondary Schools (International Journal of Scientific Research and Management (IJSRM), 2023)
Home Science as a subject has been given emphasis in the Kenya’s Basic Education Curriculum Framework as one of the core subjects in Junior School. However, fewer students selected Home Science as an optional subject in the previous education system. This study sought to investigate the relationship between perceived determinants of subject selection and students’ selection of Home Science in public secondary schools. The study investigated relationship between gender related students’ perceptions and students’ attitudes on students’ selection of Home Science subject. The study adopted a descriptive survey research design. The sample size comprised of 144 students who had selected Home Science and 124 who had not selected the subject in form three. Further, all the eight Home Science teachers and five principals of the sampled schools were purposefully sampled as key informants. Data from students was collected using a questionnaire. Interview guides were used to collect data from Home Science teachers and principals. Data were analyzed using descriptive, inferential statistics and content analysis. Results of the study revealed a statistically significant relationship between students’ gender related perceptions of Home Science subject selection [x2 (2, n = 263) = 12.501, p= .002]. Students’ attitude towards Home Science also influenced Home Science subject selection [x2 (2, n = 263) = 6.121, p= .047]. From the findings, the study recommends sensitizing learners, educators and community members about the importance of Home Science as a technical subject and to demystify gender stereotypes on the subject